A Socio-Structural Analysis of Psychological Well-Being Among Adolescents in Rural Assam: The Paradox of Community Cohesion and Relational Deficit - Puzari, Nirmali; Siddiqui, Zulfiqar Ullah; Hamed, Gahad; Abuhasan, Wael M. F.; Saleh, Emad F; Hussain, Amir; Taoutaou, Cherif (Journal of Cultural Analysis and Social Change, 2025)
This interdisciplinary study investigates the psychological well-being (PWB) of adolescents in Narayanpur Block, Lakhimpur District of Assam, India, adopting a socio-developmental perspective. Utilizing quantitative data collected from 200 students (100 males, 100 females) via the Psychological Well-Being Scale (PWBS-SDCP), the research found that 97% of participants exhibited a moderate level of overall PWB, leading to the rejection of the initial hypothesis that PWB levels would be high. Furthermore, no statistically significant gender difference was observed (p = 0.313). A granular dimensional analysis revealed a critical deficit: the lowest incidence of high PWB was observed in the dimension of Interpersonal Relations (3.5%), contrasting with moderate levels across Life Satisfaction, Efficiency, Sociability, and Mental Health. This paper utilizes sociological frameworks—specifically social capital theory, structural inequality, and the digital divide—to interpret these findings. The prevalence of moderate PWB is posited as a form of adaptive resilience to chronic rural stressors, while the non-significant gender difference is interpreted as the homogenizing effect of high community social control and rigid traditional norms. The low score in Interpersonal Relations is presented as a structural constraint, wherein strong community cohesion, paradoxically, limits individual relational autonomy and self-disclosure, compounded by socio-economic disadvantages and limited access to modern digital resources. These findings underscore the imperative for interventions that address socio-structural barriers to facilitate true eudaimonic flourishing, moving beyond merely maintaining adaptive functioning.